The effect of hydro-alcoholic celery (Apium graveolens) leaf extract on cardiovascular parameters and lipid profile in animal model of hypertension induced by fructose - Mahin Dianat; Ali Veisi; Akram Ahangarpour; Hadi Fathi Moghaddam (Mashhad University of Medical Sciences, 2015)
Objectives:Hypertension is one of the most common diseases of the modern era. This study evaluates the effect of hydro-alcoholic celery leaf extract onsystolic blood pressure (SBP), heart rate (HR) and lipid profile in animals' model of hypertension induced by fructose. Materials and Methods: Sprague Dawley rats were divided into five groups: 1) control group (free access to tap drinking water), 2) group receiving 200mg/kg celery leaf extract, 3) group receiving fructose 10%, and 4,5) receiving fructose and 100mg/kg or 200mg/kg of extract (n=8). In all groups, before and during the test period, SBP and HR were measured by Power lab system. Lipid profiles were determined by auto analysis. Repeated measurement and one way ANOVA were used for data analysis. PResults:The SBP in the fructose group significantly increased compared to control group (P